Sustainability Education in Pesantren; Understanding the Role of Shadow Organizations in Achieving Sustainable Development - Moh. Samsul Bahri; Hasan Baharun (Yayasan Avicenna, 2023)
Following up on the bankruptcy of Pesantren after decades, of course there must be a number of steps that need to be addressed or require concrete steps to maintain the sustainability of Pesantren. The purpose of this study is to find out how the role of Organizational Framing Shadow is in maintaining the Sustainability of Pesantren. This research uses a qualitative case study type approach carried out through observation, interviews and documentation. The data analysis technique starts from presenting the data, reducing the data and drawing conclusions. The results showed that: the planning and implementation of farming shadow organization in maintaining the subtainability of the Pesantren Nurul Qodim, namely: Empowerment in the field of Education, Empowerment in the social field, Empowerment in the field of Islamic da'wah. Furthermore, there is an evaluation process carried out through problem identification: mapping of service areas, classifying needs, individual problems, communities and communities to be faced, history of regional development, field observations.